An Analysis of Using Slang Word in Social Media X - Natasya Rahma; Meristika Moetia (Syntax Idea)
Slang is a form of language that is modified or shortened to make concepts shorter and easier to understand by certain groups. Although slang is informal, it can increase friendliness and enjoyment of everyday communication. Therefore, this research seeks to provide a analysis of the types of slang commonly used on social media X. This research uses qualitative research. The qualitative research used is descriptive qualitative research. The researcher chose the purposive sampling method for this research. Data collection techniques were carried out by taking screenshots and reading and writing techniques. As part of this research, social media data revealed that slang can be categorized into word types and structures. Results based on Allan & Burridge (2006) show that the forms of slang found on social media are very diverse, creative and active, including fresh and creative, flippant, imitative, acronyms and clipping. The results of the research show that, there are 3 social media accounts X that the researcher chose as samples for this research, namely Taylor Swift, Ed Sheeran, and Lady Gaga. The researchers examined 5 types of slang words, namely fresh and creative of 17%, flippant of 17%, imitative of 23%, acronym of 20% and clipping of 23%. The slang words most frequently used by the 3 samples that researchers took on social media X were Clipping and imitative with a percentage of 23%.